Records and archives legislation in Vietnam - Ha Minh Minh, Duc; Seelakate, Pimphot (D3 Perpustakaan Fakultas Vokasi Universitas Airlangga, 2024)
Background of the study: This paper consists of two parts. The first part provides the background of recordkeeping legislation in Vietnam. The second part discusses the current status of recordkeeping legislation in Vietnam. Purpose: This research aims to examine the elements of existing records and archives legislation in Vietnam by applying the ICA Guidelines: Principle for Archives and Records Legislation (2004) as a framework to analyse a crucial insight of the laws’ element. Method: The research type is a qualitative research that involves non-numerical data which is literature to gather an in-depth understanding of a case study of a specific country. Findings: The findings indicate that some elements are mandated in the existing laws such as definition of records and archives, scope of the legislation, establishment, responsibilities, and structure of the archival institution, advisory body, reporting responsibility, national archival coordination, records management, disposal, transfer of archives, access, and preservation whereas inalienability and imprescriptibly of public records and archives, acquiring records from the private sector, and sanctions are elements that can be revised in the future. Conclusion: To develop the recordkeeping legislation in Vietnam, it is suggested that (1) the laws should distinguish the terms of document, records, and archives to avoid misunderstanding and confusion for recordkeeping practices, (2) they should add more texts on managing electronic public records of government agencies, and (3) they should be coherent to Law on Access to Information 2016 to provide access to the citizens.